KAJIAN BEBERAPA METODE PEMBERIAN AIR PADI SAWAH (Oriza sativa L) VARIETAS CIHERANG DI RUMAH KACA (Study of Various Provison of Water Paddy Methods (Oryza sativa) Ciherang Variety Rice in Green House) - Riza Revita Pinem; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2017)
ABSTRACT The provision of water on a paddy is very influential to rice growth and production. This research was aim ed to study various paddy water provision methods on ciherang variety (Oryza Sativa L) in greenhouse. Parameters observed wer evapotranspiration value, potential evaporation, crop coefficient, percolation, grains weight and dry plant weight. The results show-ed that the value of crop evapotranspiration for intermiten method, humid and flooding were in an average of 1.54 mm / day, 1.60 mm / day, and 1.71 mm / day respectively. The average value of potential evaporation from vegetative phase to the ripening was 1.62 mm / day. The value of the plant's method of intermiten coeffitient, humid and flooding were in an average of 0.95, 0.99 and 1.06 respectively. The value of percolation to intermiten, humid and floodingwere in an average of 1,83 cm / day, 1 , 3 cm / day and 3.36 cm / day respectively. The plant's dry weight ofintermitent, humid and flooding were in an average of 87.5 g, 84.1 g and 77.5 g respectively and the weight of grains in intermiten, humid and flooding were in an average of 50 g, 43.3 g and 30 g respectively. Keywords : Ciherang rice, evapotranspiration, water provision, crop coefficient, percolation. ABSTRAK Pemberian air padi sawah sangat mempengaruhi pertumbuhan dan produksi padi. Penelitian ini bertujuan untuk mengkaji beberapa metode pemberian air padi sawah (Oriza sativa L) varietas ciherang di rumah kaca. Parameter yang diamati adalah evapotranspirasi tanaman, evaporasi potensial, koefisien tanaman, perkolasi, berat bulir padi dan dan berat kering tanaman. Hasil penelitian menunjukkan nilai evapotranspirasi tanaman untuk metode terputus, macak-macak dan penggenangan berturut-turut dengan rata-rata 1,54 mm/hari, 1,60 mm/hari, dan 1,71 mm/hari. Nilai rata-rata evaporasi potensial mulai dari fase vegetatif hingga pemasakan sebesar 1,62 mm/hari. Nilai koevisien tanaman untuk metode terputus, macak-macak dan penggenangan berturut-turut dengan rata-rata 0,95, 0,99 dan 1,06. Nilai perkolasi untuk metode terputus, macak-macak dan penggenangan berturut-turut dengan rata-rata 1,83 cm/hari, 1,3 cm/hari dan 3,36 cm/hari. Berat kering tanaman untuk metode terputus, macak-macak dan penggenangan berturut-turut dengan rata-rata 87,5 g 84,1 g dan 77,5 g dan berat bulir padi pada metode terputus,macak-macak dan penggenangan berturut-turut dengan rata-rata 50 g, 43,3 g dan 30 g. Kata kunci: padi ciherang, evapotranspirasi, pemberian air, koefisien tanaman, perkolasi.